2011
DOI: 10.1039/c1an15239d
|View full text |Cite
|
Sign up to set email alerts
|

Phthalide-derived novel fluoroionophores incorporating picolylamino receptors: synthesis and response to metal cations

Abstract: Phthalide derivatives incorporating mono- and di-picolylamino functionalities at the 6-position have been prepared as novel fluoroionophores and their fluorescence responses to metal cations have been investigated. These phthalides not only exhibited efficient fluorescence in an aqueous medium but also displayed fluorescence on-off response upon addition of transition-metal cations, namely Cu(2+). The 6-aminophthalide fluorophore served as the core of the fluorescent probes although it has rarely been applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…29 Recently, 6-aminophthalide derivatives have also been reported as solvent-responding fluorophores. 30,31 Imperiali et al have reported the efficient synthesis and photophysical behaviour of the 6-dimethylamino-derivatives of 2,3-naphthalimide . They demonstrated that 6-DMNs showed marked positive solvatofluorochromism and successfully applied their photophysical features to monitoring protein binding interactions.…”
Section: Introductionmentioning
confidence: 99%
“…29 Recently, 6-aminophthalide derivatives have also been reported as solvent-responding fluorophores. 30,31 Imperiali et al have reported the efficient synthesis and photophysical behaviour of the 6-dimethylamino-derivatives of 2,3-naphthalimide . They demonstrated that 6-DMNs showed marked positive solvatofluorochromism and successfully applied their photophysical features to monitoring protein binding interactions.…”
Section: Introductionmentioning
confidence: 99%